Plasma complement activation mechanisms differ in ornate (Terrapene ornata ornata) and eastern box turtles (Terrapene carolina carolina). Issue 10 (19th October 2020) - Adamovicz, Laura; Baker, Sarah J.; Merchant, Mark; Darville, Lancia; Allender, Matthew C.
Abstract: Eastern ( Terrapene carolina carolina ) and ornate ( Terrapene ornata ornata ) box turtles have robust plasma antibacterial activity, however, the mechanism behind this activity is unknown. We used sheep red blood cell (SRBC) hemolysis assays, mannan‐affinity chromatography, sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS‐PAGE), and matrix‐assisted laser desorption ionization time‐of‐flight (MALDI‐TOF) to explore the mechanisms of complement activity in box turtles. Plasma from both species demonstrated volume, time, and temperature‐dependent SRBC hemolysis, with significantly greater hemolytic activity in ornate box turtle plasma. Hemolytic activity was highly attenuated following treatment with heat, EDTA, and salicylaldoxime in both species, but was unchanged after treatment with methylamine and ammonium hydroxide. Two abundant mannan‐binding proteins (presumed C‐type lectins) were identified in eastern box turtle plasma using SDS‐PAGE and MALDI‐TOF, but ornate box turtles did not express either protein. Eastern box turtles appear to rely on the lectin pathway of complement activation while ornate box turtles utilize the alternative pathway. This study provides further evidence that mechanisms underlying immune function are not always conserved between closely related species. This finding may have important implications for explaining species differences in susceptibility to emerging threats such as disease, toxicants, and climate change. Abstract : Temperature‐dependent hemolytic activity of plasma (diluted to 30% using isotonic saline) derived from ornate box turtles ( Terrapene ornata ornata ) and eastern box turtles ( Terrapene carolina carolina ) against sheep red blood cells (SRBCs). Results represent the mean ± standard deviation of four pooled samples for each plasma dilution. Asterisks indicate values significantly different from the peak value for each species ( p  < .05). Research Highlights: Box turtle plasma lyses sheep erythrocytes in a volume, time, and temperature‐dependent manner using the complement cascade. Eastern box turtles use the lectin pathway of complement activation while ornate box turtles use the alternative pathway.